2015
DOI: 10.1086/681918
|View full text |Cite
|
Sign up to set email alerts
|

Ikaite Abundance Controlled by Porewater Phosphorus Level: Potential Links to Dust and Productivity

Abstract: Peer reviewed versionCyswllt i'r cyhoeddiad / Link to publication Dyfyniad o'r fersiwn a gyhoeddwyd / Citation for published version (APA):Glendonites are pseudomorphs of the mineral ikaite (CaCO 3 ·6H 2 O) after loss of hydration water and occur in distinctive euhedral crystalline forms, sometimes clustered as rosettes of up to tens of centimeters in diameter. While it is generally accepted that organic-rich environments, methane seeps, and high phosphate levels are important for ikaite formation, glendonite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 66 publications
(82 reference statements)
2
28
0
Order By: Relevance
“…Bischoff et al . () found that phosphate was most effective in this respect and indeed significant phosphate levels are typical of modern ikaite occurrences (Huggett et al ., ; Selleck et al ., ; Zhou et al ., ). Ikaite is probably under‐diagnosed as a primary phase (Shearman & Smith, ; Bischoff et al ., ; Buchardt et al ., ) as borne out by new discoveries such as within sea ice (Fig.…”
Section: Facies Analysismentioning
confidence: 94%
“…Bischoff et al . () found that phosphate was most effective in this respect and indeed significant phosphate levels are typical of modern ikaite occurrences (Huggett et al ., ; Selleck et al ., ; Zhou et al ., ). Ikaite is probably under‐diagnosed as a primary phase (Shearman & Smith, ; Bischoff et al ., ; Buchardt et al ., ) as borne out by new discoveries such as within sea ice (Fig.…”
Section: Facies Analysismentioning
confidence: 94%
“…If formed from an ikaite precursor, the presence of thinolite indicates a set of very specific environmental conditions at the lake bottom. Ikaite growth typically occurs in near-freezing (0 to 4°C) waters with high orthophosphate or Mg concentrations (Zhou et al, 2015), and ikaite removed from the stable temperature-pressure environment rapidly disintegrates into a mush of water and calcite (Bischoff et al, 1993a;Ito, 1998;Omelon et al, 2001). However, Purgstaller et al (2017) found that ikaite could be precipitated in laboratory conditions at water temperatures up to 12°C in solutions highly supersaturated with respect to ikaite.…”
Section: Water Temperature Indicators From Tufa Texturementioning
confidence: 99%
“…A second cooling event is thought to have occurred in the late Aptian, as a number of different proxies have indicated, e.g., d 18 O, TEX 86 , calcareous nannofossils (e.g., Herrle and Mutterlose, 2003;Mutterlose et al, 2009;McAnena et al, 2013;Bodin et al, 2015), and this is not inconsistent with our findings at Festningen. The first appearance of glendonites, which may be associated with cold water conditions (as well as specific chemical conditions; see Bischoff et al, 1993;De Lurio and Frakes, 1999;Rickaby et al, 2006;Selleck et al, 2007;and Zhou et al, 2015, for more detail), in the Carolinefjellet Formation at Festnin gen occurs at 655 m. Although macro-wood fossils above 580 m are sparse, so that using carbon-isotope stratigraphy to date their appearance more accurately is not possible, previous studies suggest that the Inkkjegla Member (in which the Carolinefjellet Formation glendonites occur) is late Aptian-early Albian in age (e.g., Nagy, 1970;Thusu, 1978; see Fig. 2).…”
Section: Record Of Climate Change In Svalbardmentioning
confidence: 99%